Analisis Peran Komunikasi Internal Dan Disiplin Kerja Terhadap Kinerja Karyawan Perusahaan Distributor Plastik Nasional - M. Yusuf Alfian Rendra Anggoro KR; Hendy Tannady; Sukma Irdiana; Ferdy Leuhery; Burhanuddin Burhanuddin (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study describes the influence of Work Discipline and Internal Communication and its effect on Employee WorkPerformance. The object of this research is PT Dwi Indah. This study discusses the theory of Work Discipline andInternal Communication. This study uses a quantitative method through a questionnaire survey which was distributeddirectly to 70 respondents which was then processed using SPSS version 20.0 with the sampling method being non-probability sampling. The results of the hypothesis test (t test) that work discipline has a significant effect on workperformance with a t count of 2,153 and a table of 1,996. Internal communication has a significant effect on workperformance with t count of 3.398 T table 1.996 with a coefficient of determination 41.7%. Work Discipline and InternalCommunication have a significant and simultaneous effect on employee work performance. The implications of thisresearch can provide an understanding for the management to pay attention to Work Discipline and good internalcommunication, especially at PT Dwi Indah. Keywords: Work Discipline, Communication, Performance